PEMAHAMAN TEKS DESKRIPSI PADA MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Ermarila Ermarila; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: As a Japanese learner, reading articles in Japanese is necessary to increase insight into the development of Japanese life in all fields, it can also improve someone's language skills. In learning Japanese there are several skills that are learned, one of them is dokkai. Dokkai (reading comprehension) is an ability that a person has in understanding reading texts and being able to conclude the information received through the reading in his own language. There are several types of Japanese text in learning dokkai, most of them are descriptive text. This research was conducted to determine the level of undestanding descriptive text in 2019 students majoring in Japanese Education, Riau University. This research uses quantitative descriptive method. This research used tests to collect the data. The participants of the research were 33 college students from 2019 students majoring in Japanese Education, Riau University. The result obtained were that understanding test results are still in the low range. Students tend to be able to remember concrete things that appear in the text. However, students are still unable to mention synonyms and explain the contents of the text.Key word : Descriptive Text , Dokkai, Understanding